Antioxidant status and clinicopathological parameters in patients with Parkinson’s disease - Miletić Vukajlović, Jadranka; Pejić, Snežana; Todorović, Ana; Valenta Šobot, Ana; Drakulić, Dunja; Pavlović, Ivan; Stefanović, Aleksandra; Prostran, Milica; Ilić, Tihomir V; Stojanov, Marina (Vojnosanitetski pregled, 2021)
Backgroun/Aim. Constant production of free radicals and antioxidants (AO) in cells is a part of normal cellular function. Their imbalance might take a part in pathophysiology of many diseases, including Parkinson’s disease (PD). Evaluation of the disease status, prooxidant-antioxidant balance (PAB) and antioxidants are being widely estimated. The aim of this study was to examine potential interaction between several AO variables: glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and PAB, and clinicopathologic features of patients with PD, particularly the Hoehn and Yahr (H&Y) stage. Methods. A multivariate analysis of variance (MANOVA) was conducted to analyze mean differences between clinicopathologic characteristics (gender, age at examination, duration of the disease, and the H&Y stage) and AO variables of PD patients and those of age/sex matched healthy controls. The study included 91 patients with idiopatic PD patients and 20 healthy persons. Results. The multivariate effect size was estimated at 0.269 (p < 0.001), implying that 27.0% of the variance of the dependent variables was accounted for the H&Y stage. Univariate tests showed that there were significant differences (p < 0.001) across the H&Y stage of all AO variables. The H&Y stage remained significant predictor after controlling for the second variable, the disease duration (p < 0.001, η2 = 0.249), and there were still significant differences across the H&Y stage of all variables, with effect size (η2) ranging from 0.132 (p = 0.011) (lnGSH) to the still high values of 0.535 (lnPAB), 0.627 (lnSOD) and 0.964 (lnCAT). Conclusion. The results indicate that higher level of oxidative stress in blood of PD patients is possibly related to the PD stage. Along with reduction of SOD and GSH levels, CAT activity was elevated in comparison to these values in healthy subjects. Furthermore, PAB was shifted toward oxidative stress.